Design and synthesis of arylthiophene-2-carbaldehydes via Suzuki-Miyaura reactions and their biological evaluation - Ali, Shaukat; Rasool, Nasir; Ullah, Aman; Nasim, Faiz-ul-Hassan; Yaqoob, Asma; Zubair, Muhammad; Rashid, Umer; Riaz, Muhammad (MDPI, 2013)
A series of various novel 4-arylthiophene-2-carbaldehyde compounds were synthesized in moderate to excellent yields via Suzuki-Miyaura cross-coupling with different arylboronic pinacol esters/acids. The synthesized products were screened for their antibacterial, haemolytic, antiurease, and nitric oxide (NO) scavenging capabilities and interestingly, almost all products turned out to have good activities. 3-(5-Formyl-thiophene-3-yl)-5-(trifloromethyl)benzonitrile (2d) revealed excellent antibacterial activity, showing an IC50 value of 29.7 µg/mL against Pseudomonas aeruginosa, compared to the standard drug streptomycin with an IC50 value 35.2 µg/mL and was also found to be the best NO scavenger, with an IC50 value of 45.6 µg/mL. Moreover, 4-(3-chloro-4-fluoro-phenyl)thiophene-2-carbaldehyde (2i) exhibited a superior haemolytic action and an outstanding urease inhibition, showing an IC50 value of 27.1 µg/mL.